Evaluasi Dedak Padi Kukus dan Suplementasi MHA (Methionine Hidroxy Analog) terhadap Kecernaan Nutrien Ransum Domba Lokal Jantan - Suprayogi, Wara Pratitis Sabar; Widyawati, Susi; Hidayah, R. (Universitas Sebelas Maret (UNS), 2009)
The research aimed to know the effect of rice bran steaming and MHA supplementation on the increasing of nutrient digestibility of local male sheep. This research used 12 local male sheeps with average of body weight 10.32 ± 1.02 kg. Treatment of rations were for P0 (60 % king grass + 40 % bran), P1 (60 % king grass +40 % steamed bran), P2 (60 % king grass + 40 % steamed bran + 1 g MHA). Design used in research was Completely Randomized Design (CRD) in one-way pattern using 3 treatments. Each treatment consisted of 4 replications. Parameters observed were dry matter intake, organic matter intake, dry matter nutritive value index and organic matter nutritive value index. The result of treatment P0, P1, and P2 for dry matter intake were 960.024; 909.426; and 926.399 g/head/day respectively, organic matter intake were 825.036; 772.665; and 796.225 g/head/day, organic matter digestibility in percent were 72.424; 73.050; and 73.068, organic matter digestibility in percent were 75.989; 76.306; and 76.239, dry matter nutritive value index were 695.396; 664.392; and 677.654 g/head/day and organic matter nutritive value index were 626.894; 589.985; and 607.649 g/head/day. The variance Analysis showed that the usage of steamed rice bran and adding of MHA given non significantly effect (P>0.5) on dry matter intake, organic matter intake, dry matter digestibility, organic matter digestibility, dry matter nutritive value index, and organic matter nutritive value index. It can be concluded that the treatments did not affect variables that were measured. Keyword : local male sheep, steamed bran, MHA, digestibility